Developing Education Skills to Enhance Skill Acquisition for Nurses in a Rural Hospital: An RNAO Fellowship From a Personal Perspective - Black, Jo-Anne (Operating Room Nurses Association of Canada Journal, 2017)
This article highlights the learning journey and successes of a rural nurse developing expertise in instructing adult learners on the skills required in an operating room setting for application in a rural hospital setting. This opportunity was made possible through a leadership and education RNAO ACFP Fellowship. This article is written based on the author’s personal experience from her individual perspective.